Socioeconomic Differences in Cause-Specific Disability Retirement in Finland, 1988 to 2009. Issue 8 (August 2016) - Polvinen, Anu; Laaksonen, Mikko; Gould, Raija; Lahelma, Eero; Leinonen, Taina; Martikainen, Pekka
Abstract : Objective: The major aim was to study socioeconomic inequalities in disability retirement due to different diagnostic causes over the period 1988 to 2009. Methods: The register data are 11% sample of people aged 30 to 64 years and living in Finland in 1987 to 2007. Incidence rates were calculated for disability retirement due to different diseases during the follow-up period 1988 to 2009. Results: The incidence of disability retirement decreased in each socioeconomic class from the early 1990s onward. Decreasing absolute socioeconomic inequalities in disability retirement due to any diagnostic cause and musculoskeletal diseases were seen in the period 1988 to 2009. Musculoskeletal diseases were the largest contributor to the overall socioeconomic inequalities in disability retirement throughout the whole study period. Conclusions: The contribution of musculoskeletal diseases to the overall socioeconomic inequalities has been large during the whole study period.